2013
DOI: 10.1021/ja401535g
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Strategy for Exploring Unknown Metabolic Pathways by Genome Mining

Abstract: Plants allocate an estimated 15-25% of their proteome to specialized metabolic pathways that remain largely uncharacterized. Here, we describe a genome mining strategy for exploring such unknown pathways and demonstrate this approach for triterpenoids by functionally characterizing three cytochrome P450s from Arabidopsis thaliana . Building on proven methods for characterizing oxidosqualene cyclases, we heterologously expressed in yeast known cyclases with candidate P450s chosen from gene clustering and microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 85 publications
0
33
0
Order By: Relevance
“…In line with these findings, a recent study by Castillo et al (2013) on triterpene-modifying enzymes in Arabidopsis showed that the C 30 -triterpene diol, arabidiol, can be degraded by CYP705A1 to a C 19 ketone product (14-apo-arabidiol). Arabidiol is produced by Pen1, also called ABDS (Xiang et al, 2006), which is highly coexpressed with CYP705A1 (Supplemental Table 2).…”
Section: Arabidiol Is the Precursor In Dmnt Biosynthesis In Arabidopsmentioning
confidence: 56%
See 1 more Smart Citation
“…In line with these findings, a recent study by Castillo et al (2013) on triterpene-modifying enzymes in Arabidopsis showed that the C 30 -triterpene diol, arabidiol, can be degraded by CYP705A1 to a C 19 ketone product (14-apo-arabidiol). Arabidiol is produced by Pen1, also called ABDS (Xiang et al, 2006), which is highly coexpressed with CYP705A1 (Supplemental Table 2).…”
Section: Arabidiol Is the Precursor In Dmnt Biosynthesis In Arabidopsmentioning
confidence: 56%
“…The reaction is induced by the root rot oomycete pathogen Pythium irregulare and treatment with the plant defense hormone jasmonic acid (JA) and contributes to Arabidopsis root defense. The CYP705A1 gene clusters with a gene encoding a pentacyclic triterpene synthase 1 (Pen1) named arabidiol synthase (here referred to as ABDS) (Xiang et al, 2006) as part of a larger triterpene biosynthetic gene cluster on chromosome 4 (Field et al, 2011;Castillo et al, 2013). Our results provide evidence for independent evolution and biosynthetic plasticity in the formation of functionally active volatiles.…”
Section: Introductionmentioning
confidence: 72%
“…These include two diterpene clusters from Oryza sativa (rice) [the momilactone and phytocassane clusters (18,19)], three triterpene clusters [the thalianol and marneral clusters from A. thaliana (20,21), the avenacin cluster from Avena strigosa (oat) (22,23)], and clusters for steroidal glycoalkaloids and other terpenes in the Solanaceae (24,25). Potential new clusters implicated in terpene synthesis have also been reported in A. thaliana (20,(26)(27)(28) and cucumber (29). The available evidence indicates that the characterized clusters have arisen within recent evolutionary history by gene duplication, acquisition of new function and genome reorganization, and that they are not products of horizontal gene transfer from microbes (reviewed in refs.…”
Section: Significancementioning
confidence: 99%
“…Although all 13 OSCs have been identified in the model plant Arabidopsis thaliana (Brassicaceae) [25], only a few triterpene skeleton oxidizing P450s have been functionally characterized [3,4]. Boutanaev et al found that CYP716A1 (At5g36110) can oxidize an unknown position of tirucalla-7,24-dien-3b-ol, the main product of PEN3 (At5g36150), which is one of the 13 OSCs in A. thaliana [2,11].…”
mentioning
confidence: 99%